A Biochemical Study to Estimate Malonaldehyde and Ceruloplasmin Oxidase Activity As Parameters Express Oxidation â€“ Antioxidation Balance for Patients With Acute Hepatitis Virus Type C - Hasan Jasim, Rasha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Oxygen free radicals play an important role in the pathogenesis of tissue damage in many pathological conditions, including liver diseases. Aim of the present study focused on the investigation the possible relationship between serum malondialdehyde level, an index of lipid peroxidation, and ceruloplasmin levels, as protective agent against lipid peroxidation, in hepatitis C virus. A group of 31 hepatitis virus type C patients enrolled in the study, while; control group consisted of 25 healthy subjects. In the present study, total proteins (g/L), malondialdehyde (ÂµM), ceruloplasmin oxidase activity (U/L) and ceruloplasmin concentration (g/L) were measured in sera samples of patients with hepatitis C virus as well as in the healthy controls.